Girls get curves : geometry takes shape - McKellar, Danica (Hudson Street Press, 2012)
"New York Times bestselling author and mathemetician Danica McKellar tackles all the angles--and curves--of geometry. Danica McKellar shattered the "math nerd" stereotype by showing girls how to ace their math classes and feel cool while doing it. Sizzling with Danica's trademark sass and style, her fourth book, Girls Get Curves, shows her readers how to feel confident, get in the driver's seat, and master the core concepts of high school geometry, including congruent triangles, quadrilaterals, circles, proofs, theorems, and more!"--